Enjoy apples free from crown rot - Sharma, M; Sharma, R (Indian Horticulture, 2019)
The collar rot or crown rot mainly caused by Phytophthora cactorum outrightly kills the plants both under nursery and field conditions, causing huge economic losses to orchardists and nurserymen. The collar rot, also known as crown rot, is prevalent in all apple-growing regions in the world including India. The disease often occurs in low-lying areas in orchards with heavy, poorly-drained soils. Its incidence increases with the introduction of more dwarf rootstocks.The huge losses mostly occur in 3-4 years old plants. Diseased trees usually survive for 2 or 3 years. In severe cases, trees can be killed in a single growing season.